Factors Related to Extralaryngeal Spread in Juvenile Recurrent Respiratory Papillomatosis. (4th December 2020) - Labedz, Geraldine; Scatolini, María Laura; Ruvinsky, Silvina; Rodriguez, Hugo Anibal
Abstract : Objectives/Hypothesis: To identify factors associated to increased risk of extra‐laryngeal spread in pediatric patients with recurrent respiratory papillomatosis (RRP). Study Design: Retrospective chart review. Methods: A retrospective study was conducted evaluating the clinical charts of patients younger than 16 years with histopathologically confirmed RRP treated between January 2014 and December 2018. Characteristics of patients with and without extra‐laryngeal disease dissemination were compared. Odds ratios were calculated and multivariate logistic regression analysis was performed. Results: Data from 82 patients were analyzed. Mean age at symptom onset was 42 months. Fifteen (18.29%) patients had extra‐laryngeal spread (ELS) at time of diagnosis and in four, the disease continued to spread to other sites. Of 67 patients with disease restricted to the larynx, 17 (25.37%) developed ELS during the disease course. Human papilloma virus (HPV) typing was performed in 49 (59.8%) patients; in 28 (57.1%) HPV subtype 6 was identified and in 21 (42.9%) HPV subtype 11. ELS was found in 11 patients with serotype 11 (52.38%) and in seven patients with serotype 6 (25%) ( P = .048). Statistically significant differences for ELS were also found for age at diagnosis younger than 5 years ( P = .045), presence of tracheostomy ( P = .031), and need for adjuvant therapy ( P = .010). Conclusions: Age at diagnosis of RRP younger than 5 years and presence of tracheostomy were factors related to ELS. A statistically significant association between infection with HPV subtype 11 and ELS were also observed. Adjuvant medication might be considered a protective factor against ELS. Laryngoscope, 131:1652–1656, 2021